Association between Serum Vitamin C and the Blood Pressure: A Systematic Review and Meta-Analysis of Observational Studies. (1st May 2020) - Ran, Li; Zhao, Wenli; Tan, Xiaodong; Wang, Hongwu; Mizuno, Kaito; Takagi, Ken; Zhao, Ye; Bu, Huaien
Abstract : Background . Hypertension is regarded as a major and independent risk factor of cardiovascular diseases, and numerous studies observed an inverse correlation between vitamin C intake and blood pressure. Aim . Our aim is to investigate the relationship between serum vitamin C and blood pressure, including the concentration differences and the correlation strength. Method . Two independent researchers searched and screened articles from the National Library of Medicine, Cochrane Library, Web of Science, China National Knowledge Infrastructure, VIP databases, and WANFANG databases. A total of 18 eligible studies were analyzed in the Reviewer Manager 5.3 software, including 14 English articles and 4 Chinese articles. Results . In the evaluation of serum vitamin C levels, the concentration in hypertensive subjects is 15.13 μ mol/L lower than the normotensive ones (mean difference = − 15.13, 95% CI [-24.19, -6.06], and P = 0.001 ). Serum vitamin C has a significant inverse relation with both systolic blood pressure (Fishe r ' s Z = − 0.17, 95% CI [-0.20, -0.15], P < 0.00001 ) and diastolic blood pressure (Fishe r ' s Z = − 0.15, 95% CI [-0.20, -0.10], P < 0.00001 ). Conclusions . People with hypertension have a relatively low serum vitamin C, and vitamin C is inversely associated with both systolic blood pressure and diastolic blood pressure.